Hybrid SPECT/CT imaging of sentinel nodes in esophageal cancer: first results. (May 2013) - Tsai, Jon A; Celebioglu, Fuat; Lindblad, Mats; Lörinc, Esther; Nilsson, Magnus; Olsson, Annie; Lundell, Lars; Axelsson, Rimma
Background: Sentinel node (SN) biopsy in esophageal cancer has the potential of becoming an important tool for ruling out the presence of lymph node metastases in patients opted for less extensive surgery without neoadjuvant treatment. Purpose: To investigate preoperative SN imaging in esophageal cancer using hybrid single photon emission computed tomography (SPECT)/CT. Material and Methods: Eight patients with esophageal cancer scheduled for thoracoabdominal esophagectomy after neoadjuvant treatment, underwent endoscopic submucosal injection of 99m Tc-nanocoll the day before surgery, followed by imaging with SPECT/CT for preoperative detection. Intraoperative detection of SNs was performed with a gamma probe. Results: SNs were identified by SPECT/CT in 7/8 cases (88%) and by gamma probe in all cases. The median number of identified lymph node stations with SN in the operating field was 1 (range 0–2) for SPECT/CT and 1 (range 1–3) for gamma probe. The median distance between the perceived location of the respective SN according to SPECT/CT and the location identified with the gamma probe was <5 mm (range <5–15 mm). In one patient who had a complete histologic response to neoadjuvant treatment in the primary tumor, there was one single metastasis that was not contained in one of the SNs. Conclusion: Preoperative identification of sentinel nodes with hybrid SPECT/CT after endoscopic injection of radiocolloid is a technique with obvious potential for SN mapping in esophageal cancer.